The Impacts of the Inquiry Learning Model and Learning Motivation on Fraction Problem-Solving Ability in Elementary Schools - Marni, Yulia; Hadiyanto; Ahmad, Syafri; Zaini, Melva (Universitas Jambi, Indonesia, 2023)
This research was quasi-experimental with a population of fourth-grade students at SD Negeri 06 Lasi Mudo and SD Negeri 08 Kubang Duo, Canduang District. Research data was obtained from test results and questionnaires. In addition, data analysis indicated a significant difference in the ability to solve Fraction problems between the inquiry and conventional models. The results of data analysis using the two-way ANOVA test obtained a sig value of 0.04 < 0.05 indicated a significant difference in learning outcomes between the inquiry and conventional models in learning motivation, but for low motivation, the sig. of 0.746>0.05 concluded that there was no significant influence between the inquiry model and learning motivation. The test results of learning models and learning motivation on Fraction problem-solving abilities through the two-way ANOVA test obtained an f-count of 3.123 with an F-table of 4.034. It showed no interaction happened between inquiry, conventional learning models, and learning motivation in Fraction problem-solving abilities in elementary schools.